(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Vocabulary mastery is a crucial component of English language learning. Using Instagram as a learning medium offers visual and interactive activities that support students’ vocabulary acquisition. This study aimed to examine the difference in English vocabulary mastery before and after the implementation of Instagram-based interactive learning among eighth-grade students at SMP Negeri 4 Palopo. The study employed a quantitative approach with a one-group pretest-posttest design. The sample consisted of 20 students selected through purposive sampling. The research instrument was a 30-item vocabulary test administered before and after the four-session learning intervention. Learning activities utilized features such as posts, captions, Stories, polls and quizzes, comments, and Reels. Data were analyzed using descriptive statistics and a paired-samples t-test. The results showed that the mean score increased from 75.20 on the pretest to 88.35 on the posttest, a difference of 13.15 points. The paired-samples t-test indicated a significant difference (t = -4.82; df = 19; p < 0.001). These findings demonstrate an improvement in students’ vocabulary mastery following the implementation of Instagram-based interactive learning.